Evoking the female ‘Asexual’: Narrating the silenced self - Aoife Sadlier (2018)
In the twenty-first century, asexuality is defined as a ‘lack’ of sexual attraction. This definition is problematic as it erodes individual idiosyncrasies, assumes that everybody is sexual and that sexuality is immutable. At this juncture, a study of female (a)sexualities is long overdue. Until recently, Myra T. Johnson’s chapter on asexual and autoerotic women was perhaps the only piece written on this subject. She highlighted the dangers of reducing asexual-identified women to symbols of spiritual devotion or political consciousness at the absence of examining their lived realities, a concern that still resonates. In this piece of performative writing, which speaks to Nguyen’s ‘me-search,’ I seek to invoke the lost voice of the female asexual by weaving queer and feminist theories of sexuality with my self-narrative, which explores my journey from asexuality to autoeroticism. Drawing on Ahmed’s ‘queer phenomenology,’ which reconceptualises sexual orientation as the lived body’s relationship with time and space, I posit asexuality as a re-oriented queer sensibility. Traversing key scenes from my trajectory, I seek to convey silences, ambivalences, transitions and becomings, thus highlighting the elusiveness of identity categories. Ultimately, I wish to address Johnson’s vision by narrating the lived realities of female (a)sexualities, beyond representations.